IMPLEMENTASI METODE TOPSIS PADA DECISION SUPPORT SYSTEM UNTUK PENILAIAN MAHASISWA BERBASIS PRESTASI AKADEMIK DAN NON AKADEMIK - Rizal Furqan Ramadhan; Kunti Eliyen (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
Today the development of the industrial world and technology is growing rapidly. The development of these two fields has a significant impact on all fields of human activity, one of which is the field of education. The influence of the times has pushed the output of higher education to be required to be able to compete and advance the country in the face of competition in the industrial era 4.0. Students in this case as outputs need to hone their academic and non-academic abilities so that they are ready to face the future in the current era of competition, so it is necessary to make an assessment of students to realize these goals. In addition, it is necessary to conduct student assessments in order to provide achievement motivation among students and create a better academic culture. In addition, it is hoped that this selection process can be adopted as a system for fostering achievement in higher education. Assessment of outstanding students in higher education can be done by using a qualified computing infrastructure. One of the mathematical methods that can be developed to assess outstanding students is the TOPSIS method. This method will later be implemented with a Decision Support System that is able to act as a data processor because it is facilitated by a database. From the results of the preference scores, several students with the highest scores were produced. Assessment based on the Decision Support System proves the effectiveness of mathematical calculations using the TOPSIS method rather than using manual methods that only use human power.